Digital Transformation of Community Activity Governance through Web-Based Documentation System Development at Karang Taruna RW 012 Jatiwaringin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Amid the growing demand for transparency, accountability, and efficiency in managing social activities, the adoption of digital systems has become a strategic solution for improving organizational governance through integrated data and documentation. This community service program was designed to support the digital transformation of Karang Taruna RW 012 Jatiwaringin by developing a web-based documentation system called RW Smart Hub. The program aimed to enhance administrators’ digital literacy, improve the efficiency of activity management, and strengthen community engagement in the digital era. It was implemented through five participatory stages: socialization, training, technology implementation, mentoring and evaluation, and sustainability strengthening. Quantitative results showed that participants’ understanding of digitalization concepts and documentation management increased significantly, from 25% before the training to 60% after, indicating a 35% improvement in digital literacy levels. Additionally, 80% of participants agreed that the system was easy to use, relevant, and beneficial for their organizational activities. The system implementation also enabled 50% of organizational activities to be documented and published digitally, contributing to improved accessibility and transparency. These outcomes demonstrate that digital transformation at the community level effectively enhances governance quality, inclusivity, and participation. This community-based digitalization model can serve as a scalable reference for improving transparency, efficiency, and participation in youth organizations.